2019
DOI: 10.3390/su11205811
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Industrial Agglomerations and Specialization in the Yangtze River Delta from 1990–2018: An Analysis Based on Firm-Level Big Data

Abstract: Although industrial agglomeration and specialization have been studied for more than 100 years, it is still a controversial field. In the era of big data, it is of great significance to study industrial agglomeration and regional specialization by using firm-level data. Based on 3,053,024 pieces of firm-level big data, the spatial evolution and spatial patterns of industrial agglomeration and specialization of 9 major industries in the Yangtze River Delta, China were revealed. Results show that: (1) the degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…For example, the industrial differences between Shanghai and Zhejiang promoted the spatial relocation of manufacturing-centered industries in the YRD region [ 45 ]. Our study also showed that the effects of industrial specialization are geographically concentrated within the YRD [ 34 ]. In addition, there was a significant spatial effect of industrial land prices in different cities on the scale of industrial diffusion.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…For example, the industrial differences between Shanghai and Zhejiang promoted the spatial relocation of manufacturing-centered industries in the YRD region [ 45 ]. Our study also showed that the effects of industrial specialization are geographically concentrated within the YRD [ 34 ]. In addition, there was a significant spatial effect of industrial land prices in different cities on the scale of industrial diffusion.…”
Section: Discussionmentioning
confidence: 67%
“…The YRD is China’s largest economic core region and one of the regions in China with the highest level of urbanization. The region has also become a focus for study of the modern urbanization process [ 31 , 32 , 33 , 34 ]. Therefore, analyzing the spatial and evolutionary associations of cities within the region from different perspectives is vital with regard to research on the urbanization process in the YRD.…”
Section: Introductionmentioning
confidence: 99%
“…is is reasonable, given that cities with a higher level of economic development often have larger budgets and may need to purchase more services/goods to support their normal operations. In addition, firms in cities with a higher GDP may be more diverse and competitive [46], resulting in more GPA outflows to other cities. e regression results suggest that the supply city's GDP plays a greater role than that of the demand city, highlighting the importance of supply cities.…”
Section: Factors Associated With the Gpa Supply-demandmentioning
confidence: 99%
“…Thus, the results of existing studies provide inconsistent evidence on the economic impact of industrial spatial agglomeration. Because of these discrepancies in theoretical and empirical results, despite more than 100 years of research, there is still much debate among scholars over the causes of industrial agglomeration; similar controversies about the measurement method of industrial agglomeration are also prevalent [42]. For example, disagreement arises over whether to use enterprise-level data or macro statistical data for research and whether to use traditional indicators (location entropy, Gini coefficient, etc.)…”
Section: Introductionmentioning
confidence: 99%